Depression im Alter: Herausforderung für eine Gesellschaft der Langlebigen = Depression in old age : challenge for aging societies - Riedel-Heller, Steffi Gerlinde; Weyerer, Siegfried (Der Nervenarzt, 2012)
SummaryDepression in old age is common and has severe consequences. The paper reviews the most recent results of population-based and primary care-based studies reporting the prevalence, course and risk factors for depression in old age. Consequences of late life depression for the individual and for the society in terms of costs of illness are outlined. Studies of health service utilization and costs showed homogeneously that healthcare costs for depressive elderly individuals are one third higher compared to non-depressive individuals even though most do not receive depression-specific treatment. Late life depression is underrecognized and undertreated and data from Germany are rare. Improvement strategies, such as collaborative care models are discussed; however, adaptation and implementation to the German context are still pending. Future demographic changes will facilitate mental health service research into late life depression.
First Online: 28 October 2012
Gesehen am 05.06.2018